Optimizing the Development of Maritime Defense In The Natuna Sea in Realizing Indonesia As The World Maritime Axis - Harris Batara (Journal of Industrial Engineering & Management Research, 2023)
the development of the South China Sea situation which is increasingly requiring special attention, where China as the largest economic and military power in the region shows a significant change in strategy. Over the past few years China has also increased its assertive stance to support territorial boundary claims, established an Air Defense Identification Zone (ADIZ) unilaterally, and maintained an attitude not to accept decisions by international courts or multilateral forums regarding SCS issues, as well as increased Chinese Navy training activities that operating all the way to the Indian Ocean, the Government of Indonesia is currently prioritizing the development of facilities and infrastructure for the placement of military forces which are considered strong enough to demonstrate Indonesia's seriousness in maintaining the territorial integrity of the Unitary State of the Republic of Indonesia. In this study, there are main problems, namely defense industry policies in supporting maritime defense in Indonesia. The method used in this research is qualitative in the form of descriptive and juridical analysis needed to analyze the problems of implementing Indonesia's seven pillars of maritime policy in order to realize Indonesia as the world's maritime axis. The results of the analysis and study of the problem show that Indonesia's defense forces are being tidied up to monitor and uphold sovereignty and will apply strict rules of engagement on the use of weapons from armaments in the Natuna region.